Identification of YfiH and the Catalase CatA As Polyphenol Oxidases of Aeromonas media and CatA as a Regulator of Pigmentation by Its Peroxyl Radical Scavenging Capacity - Chai, Baozhong; Qiao, Yunqian; Wang, He; Zhang, Xiaoming; Wang, Jiao; Wang, Choushi; Zhou, Ping; Chen, Xiangdong (Frontiers in Microbiology, 2017)
Pyomelanin is the major constituent of pigment in melanogenic Aeromonas strains of bacteria. However, eumelanin, synthesized from tyrosine via L-DOPA and polyphenol oxidases, may also be present in this genus since L-DOPA is frequently detected in culture fluids of several species. To address this question, we used a deletion mutant of A. media strain WS, in which pyomelanin synthesis is completely blocked under normal culture conditions. When tyrosine was supplied to the medium, we observed residual melanin accumulation, which we interpret as evidence for existence of the DOPA-melanin pathway. We traced enzymatic activity in this bacterium using native-polyacrylamide gel electrophoresis. Two polyphenol oxidases: YfiH, a laccase-like protein, and CatA, a catalase, were identified. However, neither protein was critical for the residual pigmentation in pyomelanin-deficient mutant. We speculate that eumelanin synthesis may require other unknown enzymes. Deletion of yfiH did not affect pigmentation in A. media strain WS, while deletion of the CatA-encoding gene katE resulted in a reduction of melanin accumulation, but it started 9 h earlier than in the wild type. Since catalases regulate reactive oxygen species levels during melanogenesis, we speculated that CatA affects pigmentation through its peroxyl radical scavenging capacity. Consistent with this, expression of the catalases Hpi or Hpii from Escherichia coli in the katE deletion strain of A. media strain WS restored pigmentation to the wild-type level. Hpi and Hpii also exhibited polyphenol oxidase activity, suggesting that catalase may represent a new class of polyphenol oxidases.